2003
DOI: 10.3748/wjg.v9.i10.2140
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological aspects of diverticular disease of colon and role of large bowel motility

Abstract: Colonic diverticular disease (diverticulosis) is one of the most common gastrointestinal disorders in Western countries. This disorder is strictly related to aging and fibre intake, and still bears a discrete amount of morbidity. Numerous etiological co-factors have to date been implicated in the pathogenesis of the disease, yet the supporting evidence is still far from absolute. The present review considers the pathophysiology of colonic diverticular disease, with a special emphasis on factors related to abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Motility changes have been reported in patients with DD (Bassotti et al, 2003) as well as UC (reviewed in Lecci et al, 2006). Bassotti et al (2005) have reported a decrease in interstitial cells of Cajal and glial cells in DD, but no change in enteric neurons, and suggested that these changes might underlie the motor abnormalities found in DD.…”
Section: Discussionmentioning
confidence: 99%
“…Motility changes have been reported in patients with DD (Bassotti et al, 2003) as well as UC (reviewed in Lecci et al, 2006). Bassotti et al (2005) have reported a decrease in interstitial cells of Cajal and glial cells in DD, but no change in enteric neurons, and suggested that these changes might underlie the motor abnormalities found in DD.…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly localised in the left colon (descending colon and sigma) and characterised by mucosal pockets within the colonic wall around the weak zones of penetration of the vasa recta through the muscolaris propria [1][2][3]. Once diverticula are formed, they can remain asymptomatic, become symptomatic in 20% of patients [4], or can evolve toward a diverticulitis possibly complicated by abscess, obstruction, fistulization, bleeding, sepsis, or strictures (uncomplicated or complicated diverticular disease, UDD or CDD) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained in this study confirm this synergistic effect: rifaximin should eliminate the microflora (which seem to play a key role in determining both symptoms and inflammation related to diverticular disease) [5] and mesalazine should reduce the effect of the inflammatory cascade. These results are very interesting, as patients with recurrent attacks of diverticulitis may progressively be affected by fibrosis and stricturing of the colonic wall, with a consequent bacterial colonic overgrowth [30]. In such cases, high grade or complete obstruction can occur, rendering medical therapy ineffective and requiring surgery.…”
Section: Mesalazine In Combination With Rifaximinmentioning
confidence: 94%